2000
DOI: 10.1200/jco.2000.18.15.2869
|View full text |Cite
|
Sign up to set email alerts
|

Matched-Pair Analysis of Conformal High–Dose-Rate Brachytherapy Boost Versus External-Beam Radiation Therapy Alone for Locally Advanced Prostate Cancer

Abstract: Locally advanced prostate cancer patients treated with EBRT + HDR demonstrate improved biochemical control compared with those who are treated with conventional doses of EBRT alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 109 publications
(45 citation statements)
references
References 81 publications
0
44
1
Order By: Relevance
“…Also, in a matched-pair analysis that compared Յ 74 Gy Ͼ 74 Gy by Hanks et al, 15 RT dose was associated significantly with DM and cause-specific death for patients who were matched for iPSA, Gleason score, and T stage. Kestin et al 16 also did a matched-pair analysis and found that higher biologic RT doses were associated with reduced OM; however, those authors did not find any relation of dose with DM or cause-specific death. In one of the few studies wherein MVA was performed, Valicenti et al 17 found that RT dose was an independent predictor of cause-specific death and OM for patients who had Gleason scores of 8 -10.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Also, in a matched-pair analysis that compared Յ 74 Gy Ͼ 74 Gy by Hanks et al, 15 RT dose was associated significantly with DM and cause-specific death for patients who were matched for iPSA, Gleason score, and T stage. Kestin et al 16 also did a matched-pair analysis and found that higher biologic RT doses were associated with reduced OM; however, those authors did not find any relation of dose with DM or cause-specific death. In one of the few studies wherein MVA was performed, Valicenti et al 17 found that RT dose was an independent predictor of cause-specific death and OM for patients who had Gleason scores of 8 -10.…”
Section: Discussionmentioning
confidence: 97%
“…9 -11 Moreover, direct evidence that RT dose reduces DM or OM has not been conclusive. 3,[12][13][14][15][16][17] In the current report, the association of RT dose to DM and OM was examined in a population of men with prostate carcinoma who were treated relatively uniformly with three-dimensional (3D)-conformal RT. Because, over the period of the study (1989 -1997), stage migration 18 -21 and Gleason score shift [22][23][24] occurred, both of which complicate retrospective analyses of treatment changes over time, the year of treatment (YOT) was included as a covariate.…”
Section: Resultsmentioning
confidence: 99%
“…[121][122][123][124][125] We restricted our analysis to use only the RCT data on biochemical relapse and frequency of adverse events.…”
Section: Case Study 1: Full Guideline Model For Prostate Cancermentioning
confidence: 99%
“…Increasingly, conformal radiation delivery techniques have safely escalated the dose to the prostate by either increasing the number of daily fractions [1][2][3] or adding a boost [4][5][6][7]. These approaches increase the delivered bioequivalent dose (BED), and consequently the biochemical control rate, but are associated with additional treatment time or, in the case of a brachytherapy boost, an invasive procedure.…”
Section: Introductionmentioning
confidence: 99%